2021
DOI: 10.1016/j.heliyon.2021.e06402
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of quantitative diffusion weighted MR imaging between benign, malignant chondrogenic and malignant non-chondrogenic bone tumors with histopathologic type

Abstract: Objectives This study aims to determine the diffusion on weighted imaging which may help in providing characterization of Apparent Diffusion Coefficient (ADC) values in benign, malignant chondrogenic and malignant non-chondrogenic bone tumors. Material and methods A retrospective study with 84 samples was conducted from October 2017 to December 2019. The samples consisted of 44 males and 40 females; the age range of 10–73 years (mean age of 32.7 years old). A Diffusion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The highest mean of ADC value was found in chondroblastic subtype. This result was similar to a study from Yakushiji et al, in the extent of the tumor cells are more freely dispersed among the chondroid matrices in chondroblastic osteosarcoma 22,23 . This study pointed to lower ADC values for osteoblastic, small cell, giant cell rich type OS lesions reflecting higher cellularity of the tumor osteoid matrix, small round cells and giant-cell stroma respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The highest mean of ADC value was found in chondroblastic subtype. This result was similar to a study from Yakushiji et al, in the extent of the tumor cells are more freely dispersed among the chondroid matrices in chondroblastic osteosarcoma 22,23 . This study pointed to lower ADC values for osteoblastic, small cell, giant cell rich type OS lesions reflecting higher cellularity of the tumor osteoid matrix, small round cells and giant-cell stroma respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the highest mean of ADC value was found in chondroblastic subtype. This result was similar to study by Setiawati et al in 2021, where the mean of ADC value in malignant chondrogenic bone tumor was 1.84x10 -3 mm 2 . Moreover, another study by Yakushiji et al in 2009 stated that chondroblastic osteosarcoma had a higher mean of ADC value than other osteosarcoma subtypes 21,23 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4 Another study conducted by Setiawati et al in 2021 stated that the increase of osteoid matrix between chondroid matrices will increase DWI restriction and decrease ADC value. 8 The highest mean ADC value was found in chondroblastic subtype. This result was similar to study result.by Setiawati et al in 2021, where malignant chondrogenic bone tumor mean ADC value was 1.84x10 -3 mm 2 and another study by Yakushiji et al in 2009 stated that chondroblastic osteosarcoma had higher mean ADC value compared with other osteosarcoma subtypes.…”
Section: Discussionmentioning
confidence: 94%
“…This in accordance with typical characteristics of osteosarcoma. 4,8 Osteosarcoma histopathological examination results were classified into several subtypes (Table 2). The most prevalent osteosarcoma subtypes were osteoblastic osteosarcoma in 20 patients (46.5%), followed by chondroblastic subtype in 8 patients (18.6%) and giant cell rich subtype in 6 patients (14.0%).…”
Section: Resultsmentioning
confidence: 99%